Studies on antagonistic properties of extremophilic actinomycetes against the agents of fungal diseases in cereal crops under various environmental conditions (Experimental biology, 2016)
Antagonistic activity of 50 isolates of extremophilic actinomycetes was examined in vitro in different habitats - neutral (medium 1, pH 7.0), saline (medium 2 with 2.5% NaCl, pH 7.0), alkaline (medium 3 with 0.25 % Na2CO3, pH 8.0) conditions using 11 species of phytopathogenic fungi. 9 isolates exhibited high specific activity against alternariosis agents, 7 isolates - against aspergillosis agents, 13 isolates - against piriculariosis agents. Isolate K-541 showed the highest activity against all the strains of the examined test organisms belonging to genera Fusarium, Alternaria, Pyricularia, Bipolaris, Aspergillus (inhibition zone diameter is of 20-56 mm). Antibiotic activity of the isolate K-541 against fungi of the Fusarium genus is 30-45 mm in neutral conditions, 40-48 mm in salty conditions, 20-33 mm in alkaline conditions.
Keywords: extremophilic actinomycetes; phytopathogenic fungi; cereal crops